REPUBLIC OF MOLDOVA'S CROP SECTOR- DEVELOPMENT TRENDS AND ASSESSMENT OF COMPETITIVENESS AT THE INTERNATIONAL LEVEL - Alexandru STRATAN; Lica ERHAN; Eugenia LUCASENCO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The agricultural sector of the Republic of Moldova is strongly relying on the crop production sector, which has been holding an average share of about 70% of the total agricultural output, being followed by livestock sector and services. Crop sector’s importance is determined through its contribution to ensuring food security, provision of raw material for the food processing sector and also support to the livestock’s sector development. Therefore, the paper aims to evaluate the current development trends of the sector, by emphasizing its achievements on the foreign markets through assessment of its competitiveness. The used methodology is based on the scientific research methods like comparative analysis, synthesis, sectoral SWOT analysis and calculation of several competitiveness indices like Revealed Comparative Advantage, Revealed Symmetric Comparative Advantage, Trade Specialization Index and Grubel-Lloyd Index. The results present a continuous development of the sector with the need for production diversification and a competitive advantage on external markets for mostly raw material products like oil seeds, edible fruits and nuts, cereals, etc.